2015
DOI: 10.1007/s10437-015-9185-8
|View full text |Cite
|
Sign up to set email alerts
|

Lakeside View: Sociocultural Responses to Changing Water Levels of Lake Turkana, Kenya

Abstract: Throughout the Holocene, Lake Turkana has been subject to drastic changes in lake levels and the subsistence strategies people employ to survive in this hot and arid region. In this paper, we reconstruct the position of the lake during the Holocene within a paleoclimatic context. Atmospheric forcing mechanisms are discussed in order to contextualize the broader landscape changes occurring in eastern Africa over the last 12,000 years. The Holocene is divided into five primary phases according to changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 140 publications
(245 reference statements)
1
33
0
Order By: Relevance
“…In eastern Africa, the arrival of domesticated animals is difficult to precisely ascertain because the point of first entry likely occurs in the Lake Turkana region when lake levels were approaching their nadir ( Figure 4D; Wright et al, 2015). However, by 4500 years BP, domesticated cattle and an accompanying Neolithic complex, including megalithic burial features, had taken root in the region (Grillo and Hildebrand, 2013) and had nominally spread southward into the equatorial regions at approximately the same time (Wright, 2007;Prendergast, 2010;Lane, 2013).…”
Section: Third Criterion: Threshold Crossing and The Arrival Of Domesmentioning
confidence: 99%
“…In eastern Africa, the arrival of domesticated animals is difficult to precisely ascertain because the point of first entry likely occurs in the Lake Turkana region when lake levels were approaching their nadir ( Figure 4D; Wright et al, 2015). However, by 4500 years BP, domesticated cattle and an accompanying Neolithic complex, including megalithic burial features, had taken root in the region (Grillo and Hildebrand, 2013) and had nominally spread southward into the equatorial regions at approximately the same time (Wright, 2007;Prendergast, 2010;Lane, 2013).…”
Section: Third Criterion: Threshold Crossing and The Arrival Of Domesmentioning
confidence: 99%
“…In BHolocene habitation with oscillating water levels and paleoclimate of Lake Turkana, Kenya^by Wright et al (2015), a paleoecological overview of changing subsistence and climatic systems over the last 12,000 years is presented. Reconstructions of lake levels were made from OSL and radiocarbon dating of coquinas in beach ridges and an exhaustive survey of archaeological materials housed in the National Museums of Kenya formed the basis of the cultural interpretations.…”
Section: Take-away Themesmentioning
confidence: 99%
“…The North Sector lies close to the conflict-stricken Illemi triangle (Oba, 1992) and, at high water levels, crosses into Ethiopia. Conflict over fishing rights in the Omo delta has worsened over the past decade and is exacerbated by low lake levels (Kine & Achalei, 2011;Johannes, Zulu, & Kalipeni, 2015;Wright et al, 2015). Some locals warn that resource scarcity will turn Lake Turkana into an "endless battlefield" (Vidal, 2015).…”
Section: Habitat Availability and Distributionmentioning
confidence: 99%
“…In line with a higher CPUE, fishermen around the lake have reported that incomes from fishing tend to increase during periods of higher lake level (Kaijage & Nyagah, ). Over geological time scales, the species composition of Lake Turkana's fisheries has changed in relation to its water level status, with a predominance of large species during high lake stands and small species during low lake stands (Wright, Forman, Kiura, Bloszies, & Beyin, ). Furthermore, rates of primary production, which are positively correlated with fish production in lakes (Melack, ; Downing, Plante, & Lalonde, ), are linked to riverine inputs of nutrients in the system (Tebbs, Avery, & Odermatt, ).…”
Section: Introductionmentioning
confidence: 99%